LINC00673 is activated by YY1 and promotes the proliferation of breast cancer cells via the miR-515-5p/MARK4/Hippo signaling pathway - Qiao, Kun; Ning, Shipeng; Wan, Lin; Wu, Hao; Wang, Qin; Zhang, Xingda; Xu, Shouping; Pang, Da (Journal of experimental & clinical cancer research, 2019)
An increasing number of studies have shown that long noncoding RNAs (lncRNAs) play essential roles in tumor initiation and progression. LncRNAs act as tumor promoters or suppressors by targeting specific genes via epigenetic modifications and competing endogenous RNA (ceRNA) mechanisms. In this study, we explored the function and detailed mechanisms of long intergenic nonprotein coding RNA 673 (LINC00673) in breast cancer progression. Quantitative real-time PCR (qRT-PCR) was used to examine the expression of LINC00673 in breast cancer tissues and in adjacent normal tissues. Gain-of-function and loss-of function experiments were conducted to investigate the biological functions of LINC00673 in vitro and in vivo. We also explored the potential role of LINC00673 as a therapeutic target using antisense oligonucleotide (ASO) in vivo. RNA sequencing (RNA-seq), dual-luciferase reporter assays, chromatin immunoprecipitation (ChIP) assay, and rescue experiments were performed to uncover the detailed mechanism of LINC00673 in promoting breast cancer progression. In the present study, LINC00673 displayed a trend of remarkably increased expression in breast cancer tissues and was associated with poor prognosis in breast cancer patients. Importantly, LINC00673 depletion inhibited breast cancer cell proliferation by inhibiting the cell cycle and increasing apoptosis. Furthermore, ASO therapy targeting LINC00673 substantially suppressed breast cancer cell proliferation in vivo. Mechanistically, LINC00673 was found to act as a ceRNA by sponging miR-515-5p to regulate MARK4 expression, thus inhibiting the Hippo signaling pathway. Finally, ChIP assay showed that the transcription factor Yin Yang 1 (YY1) could bind to the LINC00673 promoter and increase its transcription in cis. YY1-activated LINC00673 may exert an oncogenic function by acting as a sponge for miR-515-5p to upregulate the MARK4 and then inhibit Hippo signaling pathway, and may serve as a potential therapeutic target.